The Weekend Drug; Recreational Use of Sildenafil Citrate and Concomitant Factors: A Cross-Sectional Study - Berhanemeskel Weldegerima Atsbeha; Beza Tefera Kebede; Biruktawit Shewafera Birhanu; Dawit Kumilachew Yimenu; Wudneh Simegn Belay; Chilot Abiyu Demeke (Frontiers in Medicine, 2021)
Background: Men who use erectile dysfunction medications for recreational purposes may be at increased risk of becoming psychologically dependent, which in turn could lead to psychogenic-based erectile dysfunction symptoms. Sildenafil has become one of the most commonly prescribed and abused drugs available today.Objectives: This study aimed to describe the utilization pattern and associated factors of sildenafil citrate among its users visiting community pharmacies in Gondar, Ethiopia.Methods: A facility-based cross-sectional study was conducted from March 20, 2017 to May 10, 2017, among male clients who visited community pharmacies in Gondar town, North West Ethiopia. A self-administered, structured questionnaire was used to collect data from Sildenafil users older than 18 years, that started using the drug (Sildenafil) for at least 6 months before the data collection period. A regression analysis was conducted to determine the association between study variables, and a P-value of <0.05 was considered to declare statistical significance.Results: A total of 65 men participated in the study. Of the total study participants, 33.8% were aged 25–34 years and about 40% of them had multiple sexual partners. The use of sildenafil for recreational purposes was 66.2% and was found to be higher than its use for medical purposes 33.8%. Use of the drug for <1-year duration (AOR = 34.086, 95% CI [2.90, 401.37]) and 2 years duration (AOR = 21.42: 95% CI [2.10, 218.82]) were significantly associated with its use for recreational purpose. Non-recreational use of sildenafil includes erectile problems associated with diabetes mellitus (27.1%), heart disease (9.2%), hyperlipidemia (4.2%), and relationship problems due to stress and poor communication (3.1%).Conclusion: Most men who use sildenafil citrate do so for recreational purposes, and use of sildenafil citrate for 2 years or less was associated with recreational use. There should be a collaborative effort among pharmacists, health professionals, and policymakers to improve the rational use of sildenafil.